Mediastinal lymph node resection in stage IA non-small cell lung cancer with small nodule: is it mandatory? - Kim, Dong Kwan (Journal of Thoracic Disease, 2017)
Lung cancer, one of the most popular cancers in the world, is still the leading cause of cancer related death. Until recently, the only proven screening tool for early detection of lung cancer was low-dose computed tomography (LDCT) (1). These days, the detection of small sized nodule or ground-glass opacity (GGO) has increased due to the wide spread of CT screening and enhanced technology.